Relativistic decay widths of autoionization processes: the relativistic FanoADC-Stieltjes method - Faßhauer, Elke; Kolorenč, Přemysl; Pernpointner, Markus (The journal of chemical physics, 2015)
Electronic decay processes of ionized systems are, for example, the Auger decay or the Interatomic/ Intermolecular Coulombic Decay. In both processes, an energetically low lying vacancy is filled by an electron of an energetically higher lying orbital and a secondary electron is instantaneously emitted to the continuum. Whether or not such a process occurs depends both on the energetic accessibility and the corresponding lifetime compared to the lifetime of competing decay mechanisms. We present a realization of the non-relativistically established FanoADC-Stieltjes method for the description of autoionization decay widths including relativistic effects. This procedure, being based on the Algebraic Diagrammatic Construction (ADC), was adapted to the relativistic framework and implemented into the relativistic quantum chemistry program package Dirac. It is, in contrast to other existing relativistic atomic codes, not limited to the description of autoionization lifetimes in spherically symmetric systems, but is instead also applicable to molecules and clusters. We employ this method to the Auger processes following the Kr3d−1, Xe4d−1, and Rn5d−1 ionization. Based on the results, we show a pronounced influence of mainly scalar-relativistic effects on the decay widths of autoionization processes.